Acetylcholinesterase, as a potential biomarker of naphthalene toxicity in different tissues of freshwater teleost, Anabas testudineus - Susri Nayak (Vilnius Gediminas Technical University, 2021)
Naphthalene, a Polycyclic Aromatic Hydrocarbon is widely used as a fumigant and disinfectant despite its toxic effect and is ranked as the ninth most threatening compound. The present study was carried out to determine the in vivo effect of naphthalene at different concentrations on acetylcholinesterase (AChE) enzyme activity in different tissues of Anabas testudineus. The fishes were exposed to varying concentrations of naphthalene (4.2 mgL–1, 4.4 mgL–1, 4.6 mgL–1, 4.8 mgL–1 and 5 mgL–1) for a period of 72 hours. Acetylcholinesterase enzyme activity was found to be significantly inhibited, in a dose-response manner. The inhibition percentage of AChE activity varied from 9.34–43.95% in brain tissue, 2.56–35.81% in liver tissue, 5.94–34.15% in muscle tissue and 3.92–33.75% in gills in comparison to the tissues of the control group. Maximum inhibition of acetylcholinesterase enzyme activity in treated fish was observed in the brain followed by liver, muscles, and gills. This study highlights the significance and role of acetylcholinesterase as a potential stress biomarker of naphthalene toxicity.